AN AUDITING TEACHER LOOKS AT THE CPA EXAMINATION IN AUDITING. - Moore, Francis E. (The Accounting Review, 1947)
The training of students in auditing courses for the passing of the CPA examination in auditing is, of course, considered secondary to the successful training of those students to the extent that they are enabled to enter the public accounting profession well qualified to perform expeditiously the auditing tasks assigned to them. While this examination is not the major objective of the students or their instructors, it does provide the accepted measurable means by which the technical knowledge of the applicants is judged. This article, presented from the viewpoint of one who has had years of public accounting experience and who is a teacher of auditing in a metropolitan university; reviews this medium, the auditing phase of the CPA examination, in an objective manner, and presents material for consideration and discussion on various phases relating to the subject. This paper has made a review of the examinations prepared by the Board of Examiners of the American Institute of Accountants as presented from 1942 to May, 1946.